Teknik Supervisi Individual Untuk Meningkatkan Kemampuan Guru Mata Pelajaran Fisika di SMA - Iceu Rufiana (Universitas Mathla'ul Anwar Banten, 2018)
INDIVIDUAL SUPERVISION TECHNIQUES TO IMPROVE THE ABILITY OF PHYSICS TEACHERS IN HIGH SCHOOL (SMA). The aim of this study is to know how the process of implementation of supervision techniques individual for teacher in academic supervision and improve the ability of physics teachers in the implementation of the learning process. Physics teachers who are subjects of science interest in high school still experience some obstacles in the implementation of learning. In general, the problem covers: the understanding of the Minister of National Education Regulation No. 65 of 2013 on Process Standards of Education by both teachers and principals is not evenly distributed; the implementation of academic supervision by the principal is often done just to meet the administrative demands, especially before the accreditation of schools. Based on these problems, then research on academic supervision with individual meeting supervision techniques is very important to be implemented, given the ability of teachers in the learning process is still problematic. Based on the results of the study, academic supervision with individual supervision techniques is able to competency of Physics teachers in high school (SMA).